Towards more comprehensive and multi-modal transport evaluation. - Litman, Todd (My University, 2014)
This report describes ways to make transportation planning evaluation more comprehensive and multi-modal. Conventional transport planning is mobility-based, it assumes that the planning objective is to maximize travel speed, and evaluates transport system performance based primarily on automobile travel conditions. A new paradigm recognizes that the ultimate goal of most transport activity is accessibility, which refers to people s overall ability to reach desired services and activities. This new paradigm applies more comprehensive and multi-modal evaluation, which expands the range of modes, objectives, impacts and options considered in the planning process. This is particularly important in large growing cities where increased motor vehicle traffic imposes particularly large costs, and in developing countries where a major portion of households cannot afford cars.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsplanung; Mobilität; Infrastruktur; Evaluation; Multimodalität